Sistema de control de recursos para la gestión de bienes informáticos mediante un generador de código QR con aprendizaje supervisado. - Amores Estrella, Degsy Renata (2022)
The purpose of this research project is to develop an inventory management system for computer assets that exist at the Technical University of Cotopaxi, "La Maná" extension according to the rules of the current maintenance plan in the area of technical support and direction of information and communication technologies. It will serve as a support tool to contribute to the management and control of general information on the characteristics of a computer equipment by generating inventory reports. The system will allow to view the information through a mobile device by generating QR codes. The development of the research project will contribute to the corrective maintenance process of computer equipment through the application of supervised learning techniques and the nearest neighbor algorithm, so that the system will identify a high consumption of CPU and RAM memory. As a consequence, the generation of email alerts will notify the current status of the equipment and generate maintenance shifts that will allow to the technical support area to generate a history of actions that are intended to preserve the good condition and operation of a computer equipment. For the result of the project, it is essential to implement field research techniques and interviews which will facilitate gathering information on the needs that exist to support the research project.